Art and Nation. Public sculpture in Lima - Cabanillas Delgadillo, Virgilio Freddy (2018)
We studied the public sculpture of Lima city. A large proportion of the national history is told in these pieces of art: Manco Cápac, Francisco Pizarro, José de San Martín, Simón Bolívar, Ramón Castilla, José Gálvez and the Victory on May 2, Antonio Raimondi, Miguel Grau and Francisco Bolognesi. The pieces have been analyzed with methods of the Art History (formal analysis, iconography) together with social science disciplines. In this work —draft of our doctoral thesis in Art History— we focus on an emblematic case: the monument to the hero of Arica.